Aspek Hukum Penagihan dalam Layanan Fintech Peer-To-Peer Lending: Tinjauan terhadap Prinsip Perlindungan Konsumen - Elin Maysa Arlin; Joanita Jalianery; Evi Evi; Fransisco Fransisco (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the collection mechanism regulations in Fintech Peerto-Peer Lending services based on Financial Services Authority Regulation Number 40 of 2024 and Financial Services Authority Circular Letter Number 19/SEOJK.06/2025 from the perspective of consumer protection and civil law. This research is a normative legal study with a statutory and conceptual approach. The results indicate that POJK 40/2024 provides a normative basis for collection implementation, but does not explicitly regulate operational standards regarding ethics, frequency and collection limits, resulting in unclear norms. Meanwhile, SEOJK 19/SEOJK.06/2025 regulates restrictions on device access and the use of emergency contacts, but the phrase "confirmation of presence" remains open to interpretation and has the potential for misuse. Furthermore, regulations regarding user data processing in collection activities have not been clearly formulated. Therefore, the development of more measurable collection operational standards is necessary to strengthen consumer protection in the implementation of Fintech Peer-to-Peer Lending services.